Malaria in school‐age children in Africa: an increasingly important challenge. Issue 11 (22nd August 2014) - Nankabirwa, Joaniter; Brooker, Simon J.; Clarke, Sian E.; Fernando, Deepika; Gitonga, Caroline W.; Schellenberg, David; Greenwood, Brian
Abstract School‐age children have attracted relatively little attention as a group in need of special measures to protect them against malaria. However, increasing success in lowering the level of malaria transmission in many previously highly endemic areas will result in children acquiring immunity to malaria later in life than has been the case in the past. Thus, it can be anticipated that in the coming years there will be an increase in the incidence of both uncomplicated and severe malaria in school‐age children in many previously highly endemic areas. In this review, which focuses primarily on Africa, recent data on the prevalence of malaria parasitaemia and on the incidence of clinical malaria in African school‐age children are presented and evidence that malaria adversely effects school performance is reviewed. Long‐lasting insecticide treated bednets (LLIN) are an effective method of malaria control but several studies have shown that school‐age children use LLINs less frequently than other population groups. Antimalarial drugs are being used in different ways to control malaria in school‐age children including screening and treatment and intermittent preventive treatment. Some studies of chemoprevention in school‐age children have shown reductions in anaemia and improved school performance but this has not been the case in all trials and more research is needed to identify the situations in which chemoprevention is likely to be most effective and, in these situations, which type of intervention should be used. In the longer term, malaria vaccines may have an important role in protecting this important section of the community from malaria. Regardless of the control approach selected, it is important this is incorporated into the overall programme of measures being undertaken to enhance the health of African school‐age children.